2005
DOI: 10.1002/anie.200501990
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Bowl‐Shaped, Pentacyclic Phosphonium Cage by Methylation of a Nucleophilic Phosphinidene

Abstract: Dedicated to Professor Gottfried Huttner on the occasion of his 68th birthdayPhosphinidenes, that is, carbene-analogous compounds of monovalent phosphorus (phosphanylidenes, RÀP) represent a simple class of valuable electrophilic building blocks in organophosphorus chemistry, which are usually highly reactive transients and therefore difficult to isolate. [1] However, one simple chemical trick that aids the preparation of a room-temperature stable phosphinidene is the intra-or intermolecular addition of a dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…21 I was also shown to react with MeOTf which induced a rapid dimerization of the starting material and the P-methylated intermediate to give bowl shaped 30, which features ve 5membered rings within its structure (Scheme 14). 92 DFT computations suggests that the initial methylation proceeds at the phosphorus atom. This species is subsequently trapped by the starting material, despite the predicted thermodynamic preference for methylation in a-position to the nitrogen donor atom.…”
Section: Pn-c Bond Formation Reactionsmentioning
confidence: 99%
“…21 I was also shown to react with MeOTf which induced a rapid dimerization of the starting material and the P-methylated intermediate to give bowl shaped 30, which features ve 5membered rings within its structure (Scheme 14). 92 DFT computations suggests that the initial methylation proceeds at the phosphorus atom. This species is subsequently trapped by the starting material, despite the predicted thermodynamic preference for methylation in a-position to the nitrogen donor atom.…”
Section: Pn-c Bond Formation Reactionsmentioning
confidence: 99%
“…Although cascade reactions have played, and will undoubtedly continue to play, an important role in natural product syntheses, the reaction 4 → 5 (Scheme ) represents a new type of process where a homonuclear heavy p‐block multiple bond is an integral component of the process, allowing the construction, in one synthetic operation, of the C 10 P 2 cage structure present in 5 ; this provides an interesting contrast with the multistep syntheses of the corresponding hydrocarbon systems 12. Within the wider context of cascade reactions in inorganic chemistry, we note the report by Driess and co‐workers of the formation of a phosphonium cage through methylation of a phosphanylidene 13…”
Section: Methodsmentioning
confidence: 97%
“…The availability of two lone pairs on the central phosphorus atom and facile nucleophilic addition of 1 to methyl triflate was experimentally established by Driess's group. [19] Radosevich and co-workers further revealed that compound 1 has significant electrophilic character at phosphorus center, and this property is uncommon to the typical Lewis base of σ 3 À P (C 3V point group) compounds. [17] In 2012, Radosevich et al revealed that compound 1 could serve as a platform for the catalytic reduction of azobenzene via a P(III)/P(V) redox cycle mechanism (Scheme 3).…”
Section: Geometry Constrained Group 15 Compoundsmentioning
confidence: 99%